EFFECTS OF SALICYLIC ACID TREATMENTS ON HEAT TOLERANCE, CATALASE AND POLYPHENOL OXIDASE ENZYME ACTIVITY IN CHICKPEA CV. ICCV 10 - S. GAYATRIDEVI; S. K. JAYALAKSHMI; K. SREERAMULU (The Bioscan, 2015)
The effects of different treatments of salicylic acid on growth, H 2 O 2 content, catalase, polyphenol oxidases and protein profile in seedling of chickpea cv ICCV10 were studied before and after the heat stress treatments at different time intervals. Salicylic acid at concentration of 0.8 mM was found to be an optimum for maximum thermo-tolerance. Chickpea plants subjected for heat shock at 45°C caused a significant increase in endogenous H 2 O 2 and reduced catalase activity. However PPO activity was increased as compared with the controls. Further, expression of some new proteins including heat shock proteins were observed in both of the treatments. In conclusion, SA protects chickpea seedling from heat shocks at 50ºC.